Aplicación del diagrama de Ishikawa para determinar el origen del descalibrado de espesores de la primera transformación de la madera, Iquitos, Loreto 2022 - Bardales Bazan, Jhordan Dario (2023)
The present study has been carried out in the Wood transformation plant of the company TRONCO SAC, located at 980 Navarro Cauper Avenue-Punchana, with the purpose of determining the origin of the miscalibration of thicknesses of the first transformation of the wood by applying the Ishikawa diagram. From the results obtained, according to the application of the Ishikawa Diagram, 14 deficiences were determined, of which five correspond to the state of the machinery, two to raw material, two to labor and three to organizational structure. The deficiencies related to the machinery are the most important since resolving each of them would allow the percentage of defects to be greatly lowered. The plant personnel is not fully trained, likewise the company has personnel who have no experience in handling machinery and a significant number of workers who do not asume labor awareness. It is necessary for the company to hire the services of a suitable profesional to manage it with greater scientific rigor. The company must implement a flat organization for the management decision making. The company does not have an anual maintenance program for machinery, which generates greater problems. There is no business planning, only economic management of the company by management.